(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Academic freedom is one of the important elements of the establishment of higher education institutions for promoting a holistic and integrated education in order to produce knowledgeable human capital. Article 10 of the Federal Constitution clearly states that it all citizens have the right and freedom to express their views freely. From the said provisions of the Federal Constitution, there are many other legal provisions that have an impact on academic freedom in Malaysia. These include the Penal Code (Act 574), the Defamation Act 1957, the Sedition Act 1948, the Printing Presses and Publications Act 1984, the Official Secrets Act 1972, the Communications and Multimedia Act 1998, the University and University Colleges Act 1971, the constitution of every educational institution in Malaysia and others. A knowledge-based society should be given the right and freedom to express any ideas, findings or reforms that can be channeled to the relevant parties for the development of the country. However, limiting the space for these rights and freedoms will result in an "infertile" climate of thinking within local society, which will eventually lead to a reduction in intellectualism. Therefore, this article is designed to provide the concepts, scope and other factors that are considered appropriate to help the public understand the reality of the situation and how it can lead to the formation of a knowledge society as outlined in the Malaysian education system. Keywords: Academic freedom, role, strengthening of education system, knowledge society